2013
DOI: 10.1186/1748-717x-8-210
|View full text |Cite
|
Sign up to set email alerts
|

Helical tomotherapy: an innovative radiotherapy technique for the treatment of locally advanced oropharynx and inoperable oral cavity carcinoma

Abstract: BackgroundTo report our initial clinical experience of helical tomotherapy (HT) in the treatment of locally advanced oropharynx and inoperable oral cavity cancer.MethodsBetween February 2008 and January 2011, 24 consecutive patients, 15 with oropharyngeal cancer and 9 with oral cavity cancer were treated with exclusive radiotherapy or concomitant chemoradiotherapy. Simultaneous integrated boost (SIB) in 30 fractions scheme was prescribed to all patients, using Helical Tomotherapy. Doses administered to primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 18 publications
0
14
5
Order By: Relevance
“…Specifically, the low rate of long-term gastrostomy use (>12 months) was comparable to the rates reported by Nguyen et al 37 and Kimura et al 35 Oral mucositis data is the only other acute toxicity available for comparison, however, across the studies that have reported results, the incidence of grade 3 mucositis varies widely from 0%-72%. 46 The incidence of grade 2 dysphagia in that study was more than twice the rate of 29% observed in the current study. Dysphagia outcomes have only been reported in 1 helical IMRT study to date.…”
Section: Comparison With Existing Helical Intensity-modulated Radiocontrasting
confidence: 43%
See 1 more Smart Citation
“…Specifically, the low rate of long-term gastrostomy use (>12 months) was comparable to the rates reported by Nguyen et al 37 and Kimura et al 35 Oral mucositis data is the only other acute toxicity available for comparison, however, across the studies that have reported results, the incidence of grade 3 mucositis varies widely from 0%-72%. 46 The incidence of grade 2 dysphagia in that study was more than twice the rate of 29% observed in the current study. Dysphagia outcomes have only been reported in 1 helical IMRT study to date.…”
Section: Comparison With Existing Helical Intensity-modulated Radiocontrasting
confidence: 43%
“…Dysphagia outcomes have only been reported in 1 helical IMRT study to date. 46 The incidence of grade 2 dysphagia in that study Indicates results 20% or lower than the current study.…”
Section: Comparison With Existing Helical Intensity-modulated Radiocontrasting
confidence: 37%
“…Rates of grade 2 dysphagia range widely from 11-70%, and grade 3 dysphagia ranged from 0-53% (Donato et al, 2013;Hsieh et al, 2014;Santa Cruz et al, 2018;Van Gestel et al, 2015), with a combined grade 2/3 report at 80% (Kong et al, 2013). One retrospective study found younger patients had higher rates of dysphagia, whilst older patients experienced worse xerostomia and pain (Santa Cruz et al, 2018).…”
Section: Helical Imrt and Dysphagia And Related Toxicitiesmentioning
confidence: 99%
“…One retrospective study found younger patients had higher rates of dysphagia, whilst older patients experienced worse xerostomia and pain (Santa Cruz et al, 2018). With regards to oral mucositis, the reported incidence of grade 3 mucositis also ranges widely from 0-76%, with the majority of reports greater than 50% (Chen et al, 2011;Donato et al, 2013;Kreps et al, 2016;Kruser et al, 2013;Santa Cruz et al, 2018;Shueng et al, 2010;Van Gestel et al, 2015). There are a smaller number of studies reporting results for grade 2 mucositis ranging from 30-90% (Donato et al, 2013;Kreps et al, 2016;Kruser et al, 2013;Shueng et al, 2010).…”
Section: Helical Imrt and Dysphagia And Related Toxicitiesmentioning
confidence: 99%
See 1 more Smart Citation